Influência do fluxo elongacional na dispersão de celulose nanocristalina em polipropileno - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The main challenge in the production of nanocomposites is to obtain a homogenous dispersion of dispersed phase in the matrix, mainly when are used apolar thermoplastics matrices, like polypropylene (PP), reforced with polar nanoparticles as nanocristaline cellulose (NCC). For improve the dispersion of nanoparticulas there are some alternatives like chemical modifications, “in-situ” polymerization and different types of flow applied during the incorporation of the particles in the matrix. The use of an elongational flow dispositive is an alternative to generate a better dispersive and distributive mixture. The goal of this work was evaluate the influence of the elongacional flow in the dispersion of the commercial CNC by Celluforce in a PP matrix. For this, was utilized an elongational mixture dispositive with hyperbolic sections (D-MECH), this sections are divergent and convergent and are capable of generate constant rates of elongational deformations during the flow. Were also produced nanocomposites in a mini single-screw extruder and combining the two methods, i.e., melt mixing in the extruder, pelletizing the extrudate, and subsequently using the D-MECH. In total, were produced 15 compositions, in which are changed the NCC content (0, 2 e 5%), the processing speed when produced in D-MECH (2, 5 e 10 mm/min), the presence of compatibilizer and the processing method used. Were realized morphological and thermal evaluation in order to characterize the commercial NCC. The thermogravimetric analysis exhibited that the yellowing caused in the compositions processed in 2 mm/min is resulted by the low thermal stability of NCC. By transmission electronic microscopy was obtained the aspect ratio of the nanocellulose, which is around 22. The analyzes of nanocomposites were based on morphological, thermal and rheological characterizations. The morphological characterization showed the efficiency of the elongacional flow to disperse the nanoparticles in the compositions with 2% of NCC, mainly when the compatibilizer was used. In the compositions with 5%, there were no significant differences in the dispersion using the different processing types. From scanning electronic microscopy was possible observe that the interface between the matrix and particle was improved in the composition with the compatibilizer addition. The rheological results indicated that the nanocellulose presence enhanced the complex viscosity of nanocomposites, as well as the storage modulus. The thermal characterization showed that there were no significant differences in melting and crystallization temperatures of nanocomposites with NCC addition. The degree of crystallinity changed only in the composition with compatibilizer.
Keywords: Nanocompósitos; nanocelulose; fluxo elongacional; dispersão; Nanocomposites; nanocellulose; elongational flow; dispersion; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA